166k views
3 votes
Solve the inequality for x. Show each step of the solution.

8x>6(3x-1)- 14

1 Answer

4 votes

Answer:

x=4

Explanation:

Simplifying

8x + -6 = 3x + 14

Reorder the terms:

-6 + 8x = 3x + 14

Reorder the terms:

-6 + 8x = 14 + 3x

Solving

-6 + 8x = 14 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-6 + 8x + -3x = 14 + 3x + -3x

Combine like terms: 8x + -3x = 5x

-6 + 5x = 14 + 3x + -3x

Combine like terms: 3x + -3x = 0

-6 + 5x = 14 + 0

-6 + 5x = 14

Add '6' to each side of the equation.

-6 + 6 + 5x = 14 + 6

Combine like terms: -6 + 6 = 0

0 + 5x = 14 + 6

5x = 14 + 6

Combine like terms: 14 + 6 = 20

5x = 20

Divide each side by '5'.

x = 4

Simplifying

x=4

answer x=4

User Hawkeye
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.